New Constitution, New Europe: What About (Fiscal) Federalism? - Rui Henrique Alves (European Regional Science Association (ERSA), 2004)
More than fifty years after the Schuman Declaration, Europe is still far from a real Political Union. In fact, Europe faces an important imbalance between the two sides of the integration process, appearing as an important actor in the international economic scenario, but as a minor actor in the international political arena. In this paper, we start by arguing that the “small steps” strategy that led Europe until the present situation is no longer sufficient to let the Union efficiently overcome its present deficits and challenges. So, we call for an important change in the institutional and economic organisation of the EU, towards a model of largely decentralised federalism. By examining the present challenges for EU and the characteristics of the proposal for an European Constitution designed by the Convention, as well as comparing the main federal systems existing in the world today, we argue that the mentioned proposal is not enough to give the EU a strong voice both in the political and the economic areas. In this context, we discuss the design of an adequate institutional framework for the political organisation of the EU, presenting an alternative proposal based on the characteristics of a truly federal system, also as its consequences in what concerns the design and implementation of European economic policies. Keywords: European Union, Political Union, Federalism, Fiscal Federalism, European Constitution
Keywords: 330; European Union; Political Union; Federalism; Fiscal Federalism; European Constitution